PENGARUH MEDIA VIDEO ANIMASI TERHADAP PERBEDAAN HASIL PRE-TEST DAN POST-TEST SISWA KELAS IV B DAN IV C SDN KARAWANG KULON II PADA MATERI KISAH NABI MUHAMMAD SAW MEMBANGUN KOTA MADINAH - 'Atika, Risya; Subagja, Robie Wahab; Yalianto, Siti Nur Amanah; Amani, Suci Jaoharoh; Azizah, Syifa Nur; Sari, Widiarti Permana; Ramdhani, Khalid (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
The aim of this research is to find out how the use of animated videos impacts student learning outcomes. Learning outcomes are measured by comparing the pre-test and post-test scores of students in classes IV B and IV C at SDN Karawang Kulon II. The story of the Prophet Muhammad SAW building the city of Medina was chosen because understanding history is very important for Islamic religious education. This research uses a quantitative quasi-experimental approach. The results showed that students' post-test scores increased significantly after they were taught with animated videos. This media is proven to have the ability to increase students' interest, their understanding, and their retention of the material being taught. The results show that the use of animated videos can be an effective and enjoyable alternative learning method for conveying religious information in elementary schools.